Aloe Vera Polysaccharides as Therapeutic Agents: Benefits Versus Side Effects in Biomedical Applications - Consuela Elena Matei; Anita Ioana Visan; Rodica Cristescu (Polysaccharides, 2025)
Aloe Vera (Aloe barbadensis Miller), a historically revered medicinal plant, has garnered great scientific attention due to its polysaccharide-rich bioactive compounds with significant therapeutic potential. This review examines the role of Aloe Vera polysaccharides as therapeutic agents in biomedical applications, highlighting their benefits as well as the risks. Traditionally recognized for its anti-inflammatory and antimicrobial effects, which are very important in wound healing, the Aloe Vera relies on its polysaccharides, which confer immunomodulatory, antioxidant, and tissue-regenerative properties. These compounds have shown promise in various applications, including skin repair, tissue engineering scaffolds, and antiviral therapies, with their delivery being facilitated via gels, thin films, or oral formulations. This review explores also their mechanisms of action and applications in modern medicine, including in the development of topical gels, dietary supplements, and innovative delivery systems such as thin films and scaffolds. Despite the promising benefits, the review addresses the possible side effects too, including allergic reactions, gastrointestinal disorders, and drug interactions, emphasizing the importance of understanding these risks for their safe clinical use. Assessing both the advantages and challenges of Aloe Vera polysaccharide medical use, this review contributes to the ongoing dialog regarding the integration of natural products into therapeutic practices, ultimately supporting informed decisions regarding their clinical application.